2005
DOI: 10.1002/ar.a.20273
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and innervation of the mystacial vibrissal follicle‐sinus complex in bearded seals, Erignathus barbatus (Pinnipedia: Phocidae)

Abstract: Vibrissal follicle-sinus complexes (F-SCs) are sensory receptors of the mammalian integument system. They are best developed within Pinnipedia. The objective of this study was to investigate the F-SCs of bearded seals (Erignathus barbatus) for benthic foraging adaptations. Bearded seals possessed approximately 244 mystacial F-SCs. In this species, F-SCs consisted of an outer dermal capsule (DC) surrounding a blood sinus system [upper cavernous sinus (UCS), ring sinus (RS), and lower cavernous sinus (LCS)] and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
127
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(148 citation statements)
references
References 46 publications
19
127
2
Order By: Relevance
“…Unlike most phocids, pups of this species start foraging before weaning . Because bearded seals prey on fishes, crustaceans, mollusks, and worms at the sea floor (Hjelset et al 1999) using their sensitive whiskers (Marshall et al 2006), the bottom phases where swim speeds drop suggest they are foraging. In the present study, all pups including the newborn demonstrated such dives.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most phocids, pups of this species start foraging before weaning . Because bearded seals prey on fishes, crustaceans, mollusks, and worms at the sea floor (Hjelset et al 1999) using their sensitive whiskers (Marshall et al 2006), the bottom phases where swim speeds drop suggest they are foraging. In the present study, all pups including the newborn demonstrated such dives.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have argued that the presence of these foramina in other synapsids (such as the cynodont Thrinaxodon) indicates that these taxa possessed enlarged vibrissae (see discussion in Estes, 1961). However, vibrissae do not leave osteological traces on the surface of the cranium in living mammals, even in taxa with highly developed vibrissae such as pinnipeds (Marshall et al, 2006;Muchlinski, 2010). Additionally, similar foramina are present in animals that lack vibrissae (such as the modern tegu Tupinambis), suggesting that these pits more likely transmitted arteries and/or nerves (Estes, 1961).…”
Section: Paleobiology Of Uf 27881mentioning
confidence: 99%
“…The vibrotactile sense of pinnipeds relies on sturdy, specialized vibrissae and supporting hypertrophied neural architecture (Ladygina et al, 1985;Marshall et al, 2006;Hyvärinen et al, 2009;Ginter et al, 2012;Mcgovern et al, 2015), and can gather information from both terrestrial and marine environments. Pinnipeds use their vibrissae for the tactile discrimination of surfaces (Dehnhardt, 1994;Dehnhardt and Kaminski, 1995;Grant et al, 2013) and the detection and following of underwater wakes (Dehnhardt et al, 2001;Gläser et al, 2011).…”
Section: Introductionmentioning
confidence: 99%